2013
DOI: 10.1007/s12639-013-0368-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative immune study on cutaneous leishmaniasis patients with single and multiple sores

Abstract: Ninety-five Iraqi patients with cutaneous leishmaniasis (CL) caused by Leishmania tropica at AL-Karama Hospital in Baghdad were included in this study. Sixty patients were with single sore and the remaining with multiple sores. The study also included 10 atopic patients and 30 healthy individuals as a control group. Cellular and humoral immune response at different stages of the disease activity (early and late) were evaluated by estimation of serum IFNc, IL-4 and total IgE antibodies using ELISA kits while, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
2
2
1
Order By: Relevance
“…Otherwise, the results of the present work appeared to disagree with the other previous Iraqi studies by (Rahi et al, 2014) and (Al-Qadhi et al, 2013). These results may be attributed to the fact that males are more exposed to the insect biting more than females due to working outdoors and also due to men are less covering than women then exposed (Al-Samarai et al, 2016).…”
Section: Discussioncontrasting
confidence: 97%
“…Otherwise, the results of the present work appeared to disagree with the other previous Iraqi studies by (Rahi et al, 2014) and (Al-Qadhi et al, 2013). These results may be attributed to the fact that males are more exposed to the insect biting more than females due to working outdoors and also due to men are less covering than women then exposed (Al-Samarai et al, 2016).…”
Section: Discussioncontrasting
confidence: 97%
“…Respectively, when compared with the negative control group (second), which reached (2.38 ± 68.3 mg/dl), (8.63± 42.01 ng/dl), respectively, as many researchers indicated in the course of their study on the effect of leishmaniasis infection on the humoral immune response. These results are consistent with the results of the study that showed that the levels of immunoglobulins in the blood serum (IgG and IgM) were elevated in patients suffering from both types (L. Major, L. Tropic )of cutaneous leishmaniasis (Al-Qadhi et al,2015). Also showed at Soong (2019) and Kima and Boussoffara et al (2013) an increase in INF-γ concentration in leishmaniasis.…”
Section: Resultssupporting
confidence: 90%
“…Seropositivity rates and antibody titers were higher among people with multiple lesions (100.0%) compared to those with single lesions (90.2%; p < 0.05). A similar finding was observed among patients with multiple CL lesions caused by L. tropica (Wright, 1903) [ 37 , 38 ], and anti- Leishmania IgG2 was shown to be directly correlated to the number of lesions in patients with diffuse cutaneous leishmaniasis caused by L. braziliensis (Vianna, 1911) [ 39 , 40 ]. Multiple lesions could be due to multiple inoculating bites by the vector.…”
Section: Discussionsupporting
confidence: 61%